Relationship marketing and the solidarity economy enterprises with customer focus - Zajonz, Bruna Tadielo; Schulz, Jéferson Réus da Silva; Possani, Laura; Brum, Tônia Magali Moraes; Dörr, Andrea Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The idea of solidarity economy aims to strengthen solidarity enterprises with a view to reproduction of social ties. Thus, the aim of this study is to discuss, based on marketing theory, the profile and preferences of customers who are present at the 10th Fair Latin American Solidarity Economy and 21st International Fair of Cooperatives, held in Santa Maria-RS in 2014. The study method consists of a field survey that was made through the application of 140 forms in visiting the Fair public on 18th, 19th and 20th July 2014. The results show that the predominant public were women. The data indicate that the public is willing to spend at the Fair to R 50.00 and that prioritize the quality of products upon purchase. Visitors prefer to acquire, to have as a souvenir of Santa Maria-RS, t-shirts and decorative objects, highlighting the Basílica da Medianeira and the Maria Fumaça as the sights they would like to have as a souvenir of the city. The idea of the solidarity in social economy enterprises appear on the social perspective carried out by marketing, which seeks that the relationship with customers to give favorably for both parties.